Axillary dissection versus non dissection in negative sentinel node biopsy patients - Elkasem, Hossam Abd Ellatif Abo; Aldardeer, Ahmed Abdel Kahaar (International Surgery Journal, 2019)
Background: The goal of this series was to compare performing axillary clearance versus none performing in patients with node biopsy negative. Methods: This study included 114 patients had breast cancer , presented with breast mass no enlarged axillary node either clinically or radiologically and all patients had negative sentinel lymph node intraoperatively those patients presented to Sohag Cancer Center and General Surgery Department Sohag, Egypt during the period of May 2018 to May 2019. Analysis of the clinical presentation, grade of breast cancer and radiological findings was done. All patients with above mentioned criteria were fitted for the study. Results: A total of 114 patients, all of them had sentinel lymph node negative, axillary dissection done in 55 patients of them while 59 patients had no dissection. We divided the patients in our series into group A (with axillary dissection) and group B with non-dissection; in group A 27 (49.1%) patients had lymphoedema on post-operative follow up while in group B none of patients complained from lymphoedema. Numbness was found in 11 (20%) patients among group A patients, while in group B none of patients complained from numbness. On follow up of seroma we discovered that in group A all the patients had seroma while in group B only 9 (15.3%) patients had seroma. None of our 114 patients either with or without dissection had recurrence on follow up period. Conclusions: Clearance of the axilla in sentinel node negative patients has no significant difference in overall survival but also increased rates of lymphoedema, seroma and haematoma.